Implementation of a digital chatbot to screen health system employees during the COVID-19 pandemic. (15th September 2020) - Judson, Timothy J; Odisho, Anobel Y; Young, Jerry J; Bigazzi, Olivia; Steuer, David; Gonzales, Ralph; Neinstein, Aaron B
Abstract: The screening of healthcare workers for COVID-19 (coronavirus disease 2019) symptoms and exposures prior to every clinical shift is important for preventing nosocomial spread of infection but creates a major logistical challenge. To make the screening process simple and efficient, University of California, San Francisco Health designed and implemented a digital chatbot-based workflow. Within 1 week of forming a team, we conducted a product development sprint and deployed the digital screening process. In the first 2 months of use, over 270 000 digital screens have been conducted. This process has reduced wait times for employees entering our hospitals during shift changes, allowed for physical distancing at hospital entrances, prevented higher-risk individuals from coming to work, and provided our healthcare leaders with robust, real-time data for make staffing decisions.